A research on the Educational Waqf in International Islamic University Of Malaysia (IIUM) / Wan Nuha Amani W Mohd Azam - W Mohd Azam, Wan Nuha Amani (Academy of Contemporary Islamic Studies (ACIS), 2016)
Application of the concept of waqf in education becoming trend in most universities. This is because, the unique characteristics of waqf itself that enable and facilitate the funds to be collect which can move all activities related to education able to be done. Managing waqf fund efficiently and transparent allows many good impact in a university. This study examines the waqf fund management at IIUM and challenges faced by IEF. This study examines the IEF related to the implementation of waqf funds and forms or types of funds received. In addition, this study made several proposals to enhance or improve the management of waqf funds. This study uses the method by reading secondary sources such as books, journals, articles, theses and in-depth interview with the IEF. This study can provide the experience or how IEF manage waqf funds that can give benefit to the university. This study can be used as a reference for outside parties interested in implementation educational waqf in IIUM.